Scour below a subsea pipeline in time varying flow conditions. (February 2016) - Zhang, Qin; Draper, Scott; Cheng, Liang; An, Hongwei
Highlights: We conducted a series of physical experiments to investigate time scale of local scour below a subsea pipeline under changing flow condition. In this study, two consecutive flow conditions and uniform increasing flow conditions and backfill process are considered. Different arrangements of two consecutive flow conditions, and the ramp-up current flow, wave flow and combined waves and current flow are all considered. The algorithm to accumulate the effects of the different flow conditions is described based on recent proposed time scale formulae and present experimental data. The results show that the present method gives a good agreement with the measured data. Abstract: This paper presents results of an experimental investigation into the time scale of local scour and backfill for a subsea pipeline in changing flow conditions, modelled as two consecutive but different flow conditions and as uniformly increasing flow velocities. Unidirectional current flow, waves and combined waves and current flow are all considered. Based on the results of the experiments, effective time scales of the scour and backfill are quantified and algorithms to predict the scour process in changing flow conditions are derived by accumulating the effects of the different flow conditions. It is found that these algorithms may be used to predict the scour observed in the experimental data reasonably well.